Analisis Kepatuhan Wajib Pajak Dengan Menggunakan Perspektif Etika Tandur Pari - Murtini, Tri, Dr.Zulfikar,SE,M.Si (2015)
One type of local knowledge in agriculture Java is agriculture with Pranotomongso procedures (Traditional calender of Java) using sign of nature, how we treat the natural vegetation and to create balance and harmony of nature . The purpose of this study is to find the values of wisdom and ethical concepts in horticulture rice , so it can be used as a reference behave and private actors implemented in taxpayer .This study is a qualitative research approach fenomenologi with interviews , observation , and documentation . The technique used is the snowball and the object of research are farmers in the village of Fur . In an effort to increase tax obedient needs to be done with the ethical approach which contains the values of local wisdom in the soul and conscience of the taxpayer . The findings of this research are 1 ) there are values of mutual assistance , work ethic , religious , knowledge , awareness and harmony 2 ) reflected the concept of ethics as a heart murmur , fairness , benefits , capabilities , autonomous , honesty. Keywords : Local wisdom values, Ethics , Farmers , Tandur Pari, Tax Payer.